2008
DOI: 10.1093/brain/awn146
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular enlargement as a possible measure of Alzheimer's disease progression validated using the Alzheimer's disease neuroimaging initiative database

Abstract: Ventricular enlargement may be an objective and sensitive measure of neuropathological change associated with mild cognitive impairment (MCI) and Alzheimer's disease (AD), suitable to assess disease progression for multi-centre studies. This study compared (i) ventricular enlargement after six months in subjects with MCI, AD and normal elderly controls (NEC) in a multi-centre study, (ii) volumetric and cognitive changes between Apolipoprotein E genotypes, (iii) ventricular enlargement in subjects who progresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
353
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(394 citation statements)
references
References 42 publications
35
353
2
4
Order By: Relevance
“…MRS biomarkers that reflect the metabolic status of the brain may be better suited to demonstrate target engagement and follow response to treatment compared to biomarkers reflecting amyloid and Tau pathologies in AD. In the classification analyses between older CN and AD groups within this study, Glc outperformed all other MRS metabolites, and was comparable in performance to the whole brain CSF fraction representative of the atrophy and ventricular enlargement found in AD 38, 39, 40. Moreover, it is mechanistically relevant to a promising line of AD experimental therapeutics targeting glucose metabolism.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…MRS biomarkers that reflect the metabolic status of the brain may be better suited to demonstrate target engagement and follow response to treatment compared to biomarkers reflecting amyloid and Tau pathologies in AD. In the classification analyses between older CN and AD groups within this study, Glc outperformed all other MRS metabolites, and was comparable in performance to the whole brain CSF fraction representative of the atrophy and ventricular enlargement found in AD 38, 39, 40. Moreover, it is mechanistically relevant to a promising line of AD experimental therapeutics targeting glucose metabolism.…”
Section: Discussionmentioning
confidence: 65%
“…Aside from demonstrating the ability of J‐PRESS to replicate previous findings of lower NAA in AD, this study revealed substantial elevations in Glc, Lac, and Asc in the disease. The inclusion of Glc into classification models improved their accuracy beyond that of anatomical measurement of brain atrophy 38, 39, 40. Myo‐Inositol, while not differing between groups, was nevertheless reflective of several important clinical and laboratory measures of AD severity.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, structural variability is increased as a result of the pathology, and this variability represents a challenge for segmentation techniques such as atlas warping. Ventricular volume has been shown to provide a useful marker of neuronal degeneration and thus could be used as an indicator of AD (Nestor et al, 2008). However, despite the high contrast between tissue and cerebrospinal fluid (CSF), various factors render ventricle segmentation difficult.…”
Section: Datasetsmentioning
confidence: 99%
“…In particular, enlargement of the lateral ventricles (cerebrospinal fluid-filled cavities in the interior of the cerebral hemispheres) has been consistently demonstrated and may be among the most sensitive of imaging biomarkers of AD progression (2). This enlargement is a consequence of the disease process; as surrounding healthy brain tissues atrophy, there is a corresponding increase in cerebrospinal fluid (CSF) within the ventricles.…”
mentioning
confidence: 99%